An Experiment on thermal properties and design development of a hydroceramic roof tile - Ogatis, Rea Marie V.; Juanga, Jean Marie V. (2020)
The study was conducted to design, develop and experiment on a new type of material which can help cool buildings. The material uses the concept of Hydroceramics which has been developed by researchers from the Institute of Advanced Architecture in Catalonia. The developed material has been tested through computing its thermal conductivity as well as its thermal gradient through a set up experiment against other commercially available roofing materials (regular clay tile and G.I. sheet roofing). The external surface temperature and internal surface temperature of the material were acquired in a 14-day setup. The Hydroceramic roof tile showed anaverage EST of 28.93°C and an IST of 27.52°C , while the regular clay tile showed an average EST of 28.72oC and an IST of 29.29°C, and the metal roofing/GI sheet roof showed an average EST of 30.74°C and an IST of 31.33°C. Results showed that the Hydroceramic roof clay tile showed a better performance than the roof clay tile and the metal roofing in terms of keeping the heat absorbed by the material away from the interior surface and in effect, cooling the interior of a building. When compared with other materials, Thermal Tiles, Bamboo Tiles and Bituminous Fiber Tiles showed a much higher difference in surface temperatures than the Hydroceramic roof tiles.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2020